(untitled) (Global Business Management Review (GBMR), 2020)
The present study examined the relationship between economic growth and FDI in Pakistan by utilizing the data for the time period 1975-2015. The study employed a number of statistical and econometric tools for the analysis. ADF test for stationarity of data, and ARDL approach to cointegration is used for parameter estimations. The study includes GDP growth rate, foreign direct investment, trade openness, inflation and labour force as the variables of the study. The results indicated that the association between FDI and GDP growth is negative, for Pakistan, in the long run, while the results illustrated the positive association among variables in short run. Trade openness enhances GDP growth both in the long and short run, the result also revealed.